Analysis of the Relationship between Physical Environmental Factors Air Temperature and Humidity with Airborne Germ Rates in Public Elementary Schools in the Territory Work Health Center Sumbang I, Banyumas Regency - Hari Rudijanto Indro Wardono; R. Susanti; Yuni Wijayanti; Widya Hary Cahyati (International Conference on Science, Education, and Technology, 2023)
State elementary schools play a vital role in shaping the educational environment for young children. Air quality is influenced by various physical factors, including air temperature, humidity, which can affect the presence of airborne microorganisms. This research investigates the environmental factors, including air temperature, humidity, and airborne microorganism levels, and their potential impact on indoor air quality in public elementary schools within the working area of Puskesmas Sumbang I, Banyumas Regency. The research method used is an analytical observational study with a cross-sectional design. Sampling was conducted over a specific period to obtain a representative overview. Simple linear regression statistical analysis was used to identify the relationship between environmental factors and airborne microorganism levels. Sampling was conducted over a specific period to obtain a representative overview. The results of the analysis showed a significant relationship between air temperature and humidity with the number of airborne microorganisms in elementary schools. High air temperature and low humidity tends to be associated with an increase in airborne microorganisms. This emphasizes the importance of maintaining optimal air temperature and appropriate humidity levels in the school environment. The implications of this research highlight the need for prevention and control efforts related to physical environmental factors, such as ensuring proper air temperature regulation and humidity control, to improve air quality in elementary schools. Control measures may include the use of air conditioning systems and effective ventilation management. By maintaining good air quality, it is expected that student health and overall academic performance can be enhanced.